Molecular Characterization of "True" Low-Grade IDH-Wildtype Astrocytomas. Issue 5 (7th April 2021) - Richardson, Timothy E; Hatanpaa, Kimmo J; Walker, Jamie M
Abstract: Numerous recent studies have demonstrated that the vast majority of IDH-wildtype astrocytomas with WHO grade II/III histology have clinical outcomes equivalent to IDH-wildtype glioblastomas. This has called into question the existence of an IDH-wildtype lower-grade astrocytoma (LGA) category, and the cIMPACT-NOW study group has suggested 3 molecular features which, if present, warrant upgrading IDH-wildtype LGA to glioblastoma: EGFR amplification, 7+/10−, and TERT promoter mutation. Herein, we evaluate the clinical, histologic, and molecular features of IDH-wildtype low-grade astrocytomas, defined here as infiltrative adult astrocytoma lacking histologic features of glioblastoma (microvascular proliferation and/or necrosis), IDH1/2 mutation, and all 3 of the cIMPACT-NOW update 3 factors. Compared with their counterparts with cIMPACT-NOW features of glioblastoma (LGA-C+; n = 108), IDH-wildtype LGAs lacking these features (LGA-C0; n = 36) occur in significantly younger patients, are more frequently WHO grade II, have less total copy number variation distributed across the entire genome, less frequent homozygous deletion of CDKN2A, less frequent PTEN and PIK3CA alterations, and more frequent NF1 alterations. These results suggest that although rare, a "true" IDH-wildtype LGA category does exist, and has distinct clinical and molecular features consistent with relatively beneficial clinical outcomes in these patients.